2014
DOI: 10.1007/s11097-014-9376-9
|View full text |Cite
|
Sign up to set email alerts
|

Unreflective actions? complex motor skill acquisition to enhance spatial cognition

Abstract: Cognitive science has recently moved toward action-integrated paradigms to account for some of its most remarkable findings. This novel approach has opened up new venues for the sport sciences. In particular, a large body of literature has investigated the relationship between complex motor practice and cognition, which in the sports domain has mostly concerned the effect of imagery and other forms of mental practice on motor skill acquisition and emotional control. Yet recent evidence indicates that this rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 86 publications
(83 reference statements)
2
6
0
Order By: Relevance
“…First, our study corroborated the advantage of divers in the OC condition because the divers had a faster RT, independent of the angular disparities, and smaller standard deviations of RTs at higher angular disparities than the nonathletes. These findings confirmed that same-different judgements of cubes could also be embodied by sport experts, which was supported by the findings showing that experience with spatial activities could be transferred to higher cognitive abilities, such as mental rotation ( Moreau, 2015 ). The results were consistent with some studies ( Jansen & Lehmann, 2013 ; Jansen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 75%
“…First, our study corroborated the advantage of divers in the OC condition because the divers had a faster RT, independent of the angular disparities, and smaller standard deviations of RTs at higher angular disparities than the nonathletes. These findings confirmed that same-different judgements of cubes could also be embodied by sport experts, which was supported by the findings showing that experience with spatial activities could be transferred to higher cognitive abilities, such as mental rotation ( Moreau, 2015 ). The results were consistent with some studies ( Jansen & Lehmann, 2013 ; Jansen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 75%
“…The association of perceptual-motor adaptation ability and strategic game skill with the efficiency of inhibitory function might reflect the cognitive advantage deriving from practicing movement and sport activities that have the characteristics of an enriched environment as it is conceived within an embodied framework of cognition (Moreau, 2015). This supports the suggestion that the cognitive effort required to coordinate complex movements and to cope with the cognitive demands of strategic sports might foster the development of domain-general inhibitory ability that is not only useful for the sport domain.…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to contribute unifying the views on the exercise and cognition interaction in adolescents that emphasize the role played by either health-related physical fitness (Herting & Nagel, 2012;Pindus et al, 2015), or development-and learning-related motor fitness (Rigoli et al, 2012a,b), or performance-related sport skills , the main aim of the present cross-sectional study was to evaluate whether physical and motor fitness and sport game skills are predictive of executive function efficiency in adolescence. Moreau (2015) has highlighted the bydirectionality of the relationship between motor experiences and higherlevel cognition and emphasized how the cognitive demands inherent in complex motor learning and sport tasks that impact motor fitness and sport proficiency may also lead to physiological changes in the brain that positively influence executive function efficiency. Thus, we hypothesized that not only physical fitness, but also the abilities and skills deriving from exercising goal-directed complex movements and strategic sport actions may be predictors of executive function efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, activity at primary sensory and motor areas, parietal operculum, anterior and posterior cerebellum, caudal premotor areas and fronto-parietal areas has been found related to movement execution [57]. Somatotopic, peripersonal and spatial sensory data are integrated into a dynamic neural representation, which conforms the physiological body schema and permits the control over every body part and therefore movement or navigation in space [60,61]. Motor control disturbances found in patients with a TMD have been described as reduced muscles efficiency, altered chewing movement during mastication and swallowing performance [62][63][64].…”
Section: Motor and Somatosensory Disturbances In Cofpmentioning
confidence: 96%